Coping strategies and mental health during COVID-19 lockdown. (4th March 2021) - Budimir, Sanja; Probst, Thomas; Pieh, Christoph
Abstract: Background: COVID-19 pandemic lockdown measures changed the everyday lives of people around the world. Aims: To evaluate the effects of different coping strategies on mental health during COVID-19 lockdown. Methods: A representative sample for Austria was recruited through Qualtrics ® in a period of 4 weeks after the lockdown started. Measurements were coping inventory (SCI), psychological quality of life (WHO-QOL BREF, psychological domain), well-being (WHO-5), depression (PHQ-9), anxiety (GAD-7), stress (PSS-10), and insomnia (ISI). Regression analyses were performed with coping strategies as predictors and mental health measures as dependent variables. Results: The representative sample included N = 1, 005 respondents (52.7% women). Positive thinking, active stress coping and social support were found to be positive predictors for psychological life quality, well-being, and negative predictors for perceived stress, depression, anxiety, and insomnia. Alcohol and cigarette consumption was a negative predictor for psychological life quality, and well-being, and a positive predictor for perceived stress, depression, anxiety, and insomnia. Support in faith was a positive predictor for perceived stress, depression, anxiety, and insomnia. Conclusions: Coping strategies are significant predictors for mental health measures. Education about positive thinking, active coping, and social support could be beneficial for dealing with a decrease in mental health due to COVID-19 pandemic.